Collaborative Learning from the Participants' Perspective - Joseph L. Armstrong (Adult Education Research Conference, 2001)
Collaborative learning is generally reviewed in the literature and researched from the perspective of the facilitator. This study looks at the phenomena of collaborative learning from the perspective of the participants. This results in a different understanding of the collaborative learning process.